Ответы и объяснения

Лучший Ответ!
  • irakim
  • почетный грамотей
2013-04-30T08:56:33+00:00

1) х-у=2

  3х-2у=7

 

х=2+у

3(2+у)-2у=7

 

6+3у-2у=7

6+1у=7

1у=7-6

у=1

 

2)х+2у=8

   5х-3у=1

 

х=8-2у

5(8-2у)-3у=1

 

40-10у-3у=1

40-13у=1

-13у=1-40

-13у=-39

у=3

 

3)у-3х=-4

  2у+5х=25

 

у=-4+3х

2(-4+3х)+5х=25

 

-8+6х+5х=25

-8+11х=25

11х=25+8

11х=33

х=33:11

х=3

2013-04-30T09:04:52+00:00

1) х-у=2

  3х-2у=7

х=у+2

3(у+2)-2у=7

3у+6-2у=7

у=1

х=3

 

2)х+2у=8

   5х-3у=1

х=8-2у

5(8-2у)-3у=1

40-10у-3у=1

-13у=39

у=-3

х=14

 

3)у-3х=-4

  2у+5х=25

у=3х-4

2(3х-4)+5х=25

6х-8+5х=25

11х=33

х=3

у=5